Calcifying odontogenic cyst treated by a two-stage surgical approach and reconstructed with L-PRF membrane associated to lyophilized bovine bone graft - Portes, Juliana; Cunha, Karin Soares Gonçalves; Bravim, Bianca; Gonçalves, Sérgio; Urquiza, Marina; Conde, Danielle Castex (Journal of Oral Diagnosis, 2019)
Calcifying odontogenic cyst is an uncommon oral lesion, accounting for less than 1% of all odontogenic cysts. We report a case of a 28-year-old female with a complaint of a painless swelling on the anterior mandible area. Panoramic radiography and computed tomography showed a well-defined unilocular radiolucency with a radiopaque focal area, extending from the apical region of teeth 34 to 43. An incisional biopsy showed a cystic lesion lined by ameloblastoma-like epithelium with the presence of ghost cells and calci- fying material consistent with the diagnosis of calcifying odontogenic cyst. The treatment of choice was decompression with posterior enucleation of the lesion, and the region was filled-up with L-PRF membrane (Leukocyte – Platelet Rich Fibrin) and lyophilized bovine bone graft (Bio-Oss®). A two-stage treatment starting with decompression allows the prevention of some complications, such as fracture of the jaw or injury of noble structures and consequently, decreases the chances of recurrence. To the best of our knowledge, there are few published cases of COC treated by decompression followed by enucleation. The patient remains on follow-up and after 14 months, there is no sign of recurrence.